Pengaruh Citra Merek dan Kepercayaan Merek Terhadap Loyalitas Merek Telkomsel (Studi Pada Mahasiswa Manajemen Universitas Trunojoyo Madura) - Dwi Munisa, Miftakhul Salsabilla; Setiyarini, Triana (Jurnal Kajian Ilmu Manajemen (JKIM), 2023)
This study aims to determine the effect of brand image and brand trust on brand loyalty. The independent variables in this study are brand image and brand trust. While the dependent variable in this study is brand loyalty. This research uses quantitative methods. The sampling technique in this study used non-probability sampling techniques with purposive sampling method with a total of 100 respondents from management students of Trunojoyo University Madura who used Telkomsel data packages. The data analysis method uses multiple linear regression analysis which is processed using SPSS version 29.The results of this study indicate that: 1) Brand image variables partially affect Telkomsel brand loyalty. 2) Brand trust variables partially affect Telkomsel brand loyalty. 3) Brand image variables and brand trust simultaneously affect Telkomsel brand loyalty.